Inverse solution to heat transfer coefficient during heat assembly of aluminum alloy drill pipes. (July 2017) - Sun, Youhong; Wang, Xiaofeng; Liu, Baochang; Ding, Dali; Meng, Qingnan
With the rapid development of oil and gas industry, as well as geological exploration industry, the requirements on properties of aluminum alloy drill pipes are increasing. During heat assembly of aluminum alloy drill pipes, the cooling process inside the pipes has a direct impact on the connection performance of pipes. Thus, study of the convective heat transfer coefficient between the cooling water and the internal wall of aluminum alloy pipes is important. Conventional algorithms cannot easily solve the problem of determining the heat transfer coefficient at the complex structure of aluminum alloy drill pipes. Therefore, this article conducts a heat assembly experiment between aluminum alloy drill pipes and steel joints to obtain adequate, accurate temperature data. Based on these experimental data and an inverse heat conduction model, the heat transfer coefficients during the heat assembly process are determined by a finite element program and the differential evolution algorithm. The correlation curve between the cooling water flowrate and the convective heat transfer coefficient obtained in this article is important in the accurate prediction of heat transfer capacity and temperature field distribution during heat assembly at different cooling water flowrates. The analysis results show that the heat transfer coefficients are nonlinear functions of cooling water flowrates. The temperature is highest at location A 1 and gradually declines backward along the axis of the drill pipe. The heat transfer coefficient gradually declines backward along the axis of the drill pipe. The increasing flowrate of cooling water will cause the convective heat transfer coefficient along the axis of the drill pipe to escalate irregularly.